Does gender matter in cyberbullying perpetration? An empirical investigation. (February 2018) - Wong, Randy Y.M.; Cheung, Christy M.K.; Xiao, Bo
Abstract: Cyberbullying is a highly prevalent online misbehavior that has recently received public attention due to its potentially devastating consequences. In response to the call to understand the mechanism leading to cyberbullying perpetration, this study draws on I 3 theory to understand the decisions of young adults to engage in cyberbullying. Furthermore, it examines the influence of gender on various determinants of cyberbullying perpetration. The results of an online survey involving 208 university students reveal that both cyberbullying victimization and perceived online disinhibition enhance the intention to perpetrate cyberbullying, whereas self-control is a critical buffer that represses the propensity to cyberbully others. Our findings also show that the factors influencing cyberbullying differ in strength for male and female students. We believe that these findings not only provide a theoretical explanation of cyberbullying perpetration but also offer valuable insights for combatting cyberbullying among university students. Highlights: Drew on I 3 theory to explain individuals' decisions to perpetrate cyberbullying. Explored the role of gender in strengthening/mitigating the different forces. Extended the applicability of I 3 theory to the cyberbullying context. Differentiated three distinct determinants of cyberbullying perpetration. Found the effects of instigating and impelling forces are differed across gender.